Analysis of Compensation, Leadership Style, Work Environment and its Effect on Employee Performance with Job Satisfaction as Intervening at PT. Mitracomm Ekasarana - Pintraco Group - Donie Nahloly; Siti Safaria (Formosa Journal of Sustainable Research, 2023)
The research using quantitative approach to employees at PT Mitracomm Ekasarana - Pintraco Group, total population as the sample size. The data obtained was analyzed in SmartPLS 3. Compensation have no significant effect on Job Satisfaction, Compensation not influencing Employee Performance, Leadership style influencing job satisfaction, leadership style not influencing employee performance. Work Environment influencing Job Satisfaction, Work Environment influencing Employee Performance, Job Satisfaction influencing Employee Performance, Compensation indirectly have no significant effect on not influencing Performance through Job satisfaction, Leadership Style indirectly influencing Employee Performance through Job satisfaction, Work environment indirectly have a significant effect on Employee Performance through Job satisfaction